Transcatheter closure of tubular PDA with amplatzer plug 4 in preterm infants weighing between 900 and 3,400 g: the pros and cons - Mini, Nathalie; Schneider, Martin B. E.; Schneider, Katja (Frontiers in Cardiovascular Medicine, 2023)
Objective: To our knowledge, no prior study has focused on the outcome of PDA occlusion using an Amplatzer™ Vascular Plug 4 (AP4) in ill preterm infants. This study aims to highlight the pros and cons of AP4 in this cohort.Methods: Between 2020 and 2022, 26 ill preterm infants underwent PDA closure in our centre. The median age, weight, and gestational age were 60 days (11-180 days), 1900 g (900-3400 g), and 25 weeks (22-33 weeks), respectively. The indication of the intervention was hemodynamically significant PDA. A medical trial with non-steroid medication failed to close the ducts in all patients. Follow-up using echocardiography was done 24, 48, and 72 hours after the intervention.Results: Of 26 ducts, 21 were successfully closed with AP4. Five ducts shorter than 7 mm were unsuitable for AP4 and were closed with the Amplatzer Piccolo device. The median radiation time was 4 min (3-9 min). No early plug-related complications or deaths were documented. Plug-related jailing of the left pulmonary artery as a late complication was 9.5%, and LPA reintervention was required. All ducts were closed after 48 hours.Implantation of the AP4 using a 4 F 0.38 guide wire-compatible catheter without inserting a long sheath makes the closure of tubular ducts with this device feasible and uncomplicated with a short intervention time. However, the limited sizes with fixed lengths of the AP4 make it unsuitable for ducts wider than 5 mm and shorter than 7 mm or shorter than the chosen device length, which can increase the risk of significant left pulmonary stenosis. A wide range of plug diameters and lengths is required to accommodate the large and short ducts.